Recurrences and related characteristics of gastric cancer. - Maehara, Y. (Nature Publishing Group, 1996)
We analysed data on 1117 patients with gastric cancer who were treated by curative resection. Attention was focused on invasion and a recurrence of the cancer. Based on a univariate analysis, death following a recurrence and prognosis were related to age of the patients, size of the tumour, tumour location, tumour tissue differentiation, growth pattern, depth of invasion, lymphatic and vascular invasion and lymph node metastasis. In proportion to the growth potential, determined by the level of proliferating cell nuclear antigen (PCNA) labelling, the death related to a recurrence was increased and the prognosis was poorer. Multivariate analysis showed that the three factors of serosal invasion, PCNA labelling index and lymph node dissection were independent prognostic factors. When sites of recurrence were analysed regarding each depth of invasion, haematogenous recurrence, in particular in the liver, occurred even in cases of an early invasion and many types of recurrences, including peritoneal recurrence, were noted in patients with an advanced state of invasion.